2008
DOI: 10.1590/s0103-64402008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage period and effect of different brands of acrylic resin on the dimensional accuracy of the maxillary denture base

Abstract: The aim of this study was to evaluate the dimensional changes of denture bases made from different resins after different storage periods. For this purpose, 25 sets of plaster models/resin bases were prepared using 4 acrylic resins submitted to two types of polymerization: 1-QC-20 submitted to polymerization by microwave energy; 2-QC-20 submitted to polymerization by water hot bath; 3-Vipi Cril submitted to polymerization by water hot bath; 4-Vipi Wave submitted to polymerization by microwave energy; and 5-Ond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
1
27
0
2
Order By: Relevance
“…After three months, the two type of denture showed statistically non-significant increase in retention values over retention values at one month, this might be due to the neuromascular control and patients adaptability to their dentures. But still when we compared the retention values at three months of the flexible acrylic resin and the conventional heat cured acrylic resin, flexible acrylic resin showed statistically significant higher retention values over the conventiona lheat cured acrylic resin (9).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…After three months, the two type of denture showed statistically non-significant increase in retention values over retention values at one month, this might be due to the neuromascular control and patients adaptability to their dentures. But still when we compared the retention values at three months of the flexible acrylic resin and the conventional heat cured acrylic resin, flexible acrylic resin showed statistically significant higher retention values over the conventiona lheat cured acrylic resin (9).…”
Section: Discussionmentioning
confidence: 85%
“…It's important that patient perceive their denture as retentive during function and as esthetically agreeable in order to meet the psychodynamics required by the patient (9) .In this study denture retention obtained by using two different denture base materials, conventional heat cured acrylic resin and heat cured thermoplastic resin, was compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However Miessi et al 14 showed that when specimens are kept in water for longer periods of time (2 months) significant expansion may occur and it would damage appliance fitness. This further expansion is caused by the great capacity of resin for water sorption.…”
Section: Discussionmentioning
confidence: 99%
“…Bu safhada polimerizasyon büzülmesi tamamlanmış olacağından meydana gelen büzülme termal kökenli olup rezinlerin bileşimine bağlıdır. Gerilimler ve bunun sonucunda meydana gelen distorsiyonları gidermek için çeşitli muflalama teknikleri ve rezin formülasyonları geliştiril-mektedir (3)(4)(5).…”
Section: Gđrđşunclassified